Radiative properties of a nonsingular black hole: Hawking radiation and gray-body factor - Asier Alonso-Bardaji; David Brizuela; Marc Schneider (Journal of High Energy Physics)
Abstract We study the radiative properties of a spherical and singularity-free black-hole geometry recently proposed in the literature. Contrary to the Schwarzschild spacetime, this geometry is geodesically complete and regular, and, instead of the singularity, it presents a minimal surface that connects a trapped (black-hole) with an antitrapped (white-hole) region. The geometry is characterized by two parameters: the Schwarzschild radius and another parameter that measures the area of the minimal surface. This parameter is related to certain corrections expected in the context of loop quantum gravity to the classical general-relativistic dynamics. We explicitly compute the spectrum of the Hawking radiation and the gray-body factor. Since the gravitational potential is shallower than in Schwarzschild, the emission spectrum turns out to be colder and purer (less gray). From this, we sketch the evaporation history of this geometry and conclude that, under certain assumptions, instead of completely evaporating, the black hole naturally leads to a remnant, which provides a possible resolution to the information-loss issue.